A new species of the Genus Microbrotula (Teleostei: Bythitidae) from Cenderawasih Bay, New Guinea, Indonesia - Schwarzhans, Werner; Nielsen, Jørgen G. (Zootaxa, 2012)
Following the recent revision of Microbrotula (Schwarzhans & Nielsen, 2011), an additional nine specimens of the vivi-parous genus Microbrotula (Teleostei: Bythitidae), all caught in the Cenderawasih Bay, Irian Jaya, New Guinea, Indone-sia, were made available to us. These specimens represent a new species described here as M. geraldalleni. It belongs tothe group of species with 6 caudal and 14 pectoral fin rays and is closest to M. greenfieldi, differing in the higher dorsaland anal fin ray counts (68–73 and 61–65 vs. 62–70 and 58–61, respectively), the presence of 3 posterior mandibular pores(vs. none), 2–3 preopercular pores (vs. none), a connected squamation over the head including cheek, opercle and occiput(vs. 3 separated scale patches) and with a unique scale-less triangular window just above the opercle. Microbrotula geraldalleni may be endemic to the Cenderawasih Bay.